2018
DOI: 10.3847/1538-3881/aa9ee2
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Extragalactic Sources in the VISTA Variables in the Vía Láctea Survey

Abstract: We search for extragalactic sources in the VISTA Variables in the Vía Láctea survey that are hidden by the Galaxy. Herein, we describe our photometric procedure to find and characterize extragalactic objects using a combination of SExtractor and PSFEx. It was applied in two tiles of the survey: d010 and d115, without previous extragalactic IR detections, in order to obtain photometric parameters of the detected sources. The adopted criteria to define extragalactic candidates include CLASS STAR < _ 0 . 3 ; 1.0 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Another interesting feature of these CMDs is the branch of very dim and red sources that appears at magnitudes fainter than K s > 16 and colors J−K s > 1.3 (Z−K s > 2.3). These sources can be associated with background galaxies, as some studies suggest (Lucas et al 2008;Coldwell et al 2014;Baravalle et al 2018), although at the faintest magnitudes this sequence is expected to be heavily contaminated with the tail of Galactic stars with higher photometric errors. We note that this sequence is more noticeable in the K s vs J − K s CMD, while the previously mentioned BHB sequence manifests more clearly in the K s vs Z − K s CMD.…”
Section: Cmds Of the Galactic Bulge Fields In The Vvvmentioning
confidence: 99%
“…Another interesting feature of these CMDs is the branch of very dim and red sources that appears at magnitudes fainter than K s > 16 and colors J−K s > 1.3 (Z−K s > 2.3). These sources can be associated with background galaxies, as some studies suggest (Lucas et al 2008;Coldwell et al 2014;Baravalle et al 2018), although at the faintest magnitudes this sequence is expected to be heavily contaminated with the tail of Galactic stars with higher photometric errors. We note that this sequence is more noticeable in the K s vs J − K s CMD, while the previously mentioned BHB sequence manifests more clearly in the K s vs Z − K s CMD.…”
Section: Cmds Of the Galactic Bulge Fields In The Vvvmentioning
confidence: 99%
“…In this way, we generated a multi-band catalogue with all detected sources. SExtractor recognised and separated from the background noise all the objects with a threshold more than twice the medium brightness of the sky and spanned over at least ten connected pixels on the VVV images (Coldwell et al 2014;Baravalle et al 2018). A filter convolution was applied over the images by SExtractor with the aim being to efficiently separate low-surface-brightness objects from spurious detections.…”
Section: Automatic Detectionmentioning
confidence: 99%
“…Nevertheless, the improved extinction correction changes the mean colour to 0.988 with a standard deviation of ±0.12, which is in good agreement with the high-latitude sample. Baravalle et al (2018) also define similar colour cuts to separate star from galaxy candidates. In addition, Amôres et al (2012) and Coldwell et al (2014) found that objects selected as galaxy candidates from the VVV survey show mainly J-Ks> 1.0 colours.…”
Section: Automatic Catalogue Of Extended Sourcesmentioning
confidence: 99%
See 2 more Smart Citations